Effect of sex on glomerular filtration rate in programmed rats by prenatal dexamethasone. Issue 12 (26th June 2019) - Jain, Jyoti; Legan, Susan K.; Alhamoud, Issa; Gattineni, Jyothsna; Baum, Michel
Abstract : We have previously demonstrated that dexamethasone administered to pregnant rats during specific times during gestation results in a reduction in glomerular number and hypertension in offspring at 2 and 6 months of age. In this study, we examined the effect of prenatal dexamethasone administered daily on days 15 and 16 of gestation in male and female offspring after 1 year of age on glomerular filtration rate. The prenatal dexamethasone male group had a higher systolic blood pressure than the vehicle male group. Females had lower systolic blood pressures than the males and prenatal dexamethasone did not affect blood pressure in female offspring. Prenatal dexamethasone resulted in a reduction in glomerular filtration rate in male but not in female rats. When corrected for body weight, the control male rats had a lower glomerular filtration rate than the control female rats. Males had greater protein excretion than females and prenatal dexamethasone increased the protein excretion only in male rats. Glomerulosclerosis was also greater in male rats than females but was not affected by prenatal dexamethasone. In summary, male rats appear to have evidence of a decline in glomerular filtration rate after 1 year of age and prenatal dexamethasone programs an accelerated decline in glomerular filtration rate in male but not in female offspring. Abstract : This study shows that prenatal programming by dexamethasone causes a reduction in glomerular filtration rate in males but not female rats.